Investigation on Sustainable Source of Nutrients from Fresh and Pasteurised Sweet Potato Haulm Juice Powder - Nurhani Fatihah Mohd Hanifah; Nur Anisya Syakirah Mohd Sayuti; Syamila Mansor (Penerbit UMT, 2024)
Indexed by ERA/MyCite